Pattern of Pharyngitis and Tonsillitis Patients at ENT Clinic of Wlingi Hospital in 2019-2021 - Samuel Prasetyo; Ika Susilastining Utami (Jurnal Kedokteran Brawijaya, 2023)
A survey conducted by the Ministry of Health in 2010-2012 in seven provinces in Indonesia found that the number of ENT disease sufferers in Indonesia was approximately 35.6 million, or 16.8% of the total population. Pharyngitis and tonsillitis are examples of ENT cases often faced in daily practice. Both diseases indicate symptoms that resemble Covid-19, which has become a problem recently. This study aimed to analyze pharyngitis and tonsillitis patient visits at the ENT clinic of Wlingi Hospital during the Covid-19 in 2019-2021. Benefit of this study is to know pattern of pharyngitis and tonsillitis at the ENT clinic of Wlingi hospital in 2019-2021 during Covid-19 time. This research used a descriptive statistics method with an epidemiological cross-sectional design. The data in this study were secondary data from the medical records of ENT clinic patients at Wlingi Hospital and were analyzed univariately. Sampling in this study was done using the total sampling method. Based on medical record data at the ENT clinic of Wlingi Hospital in 2019-2021, there were 2292 visits in 2019, 1811 visits in 2020, and 1255 visits in 2021. Based on medical record data for pharyngitis and tonsillitis cases at the ENT clinic of Wlingi Hospital in 2019-2021, there were 247 pharyngitis and tonsillitis case visits in 2019, 114 pharyngitis and tonsillitis case visits in 2020, and 69 pharyngitis and tonsillitis case visits in 2021. There was a decrease in the number of pharyngitis and tonsillitis case visits in the ENT clinic of Wlingi Hospital during 2019-2021.